1985
DOI: 10.1128/iai.49.3.654-663.1985
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Candida albicans gut colonization: inhibition of Candida adhesion, colonization, and dissemination from the gastrointestinal tract by bacterial antagonism

Abstract: Antibiotic-treated and untreated Syrian hamsters were inoculated intragastrically with Candida albicans to determine whether C. albicans could opportunistically colonize the gastrointestinal tract and disseminate to visceral organs. Antibiotic treatment decreased the total population levels of the indigenous bacterial flora and predisposed hamsters to gastrointestinal overgrowth and subsequent systemic dissemination by C. albicans in 86% of the animals. Both control hamsters not given antibiotics and antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0
3

Year Published

1986
1986
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(88 citation statements)
references
References 63 publications
(38 reference statements)
0
84
0
3
Order By: Relevance
“…However, this effect was not observed with C. parapsilosis or T. glabrata. Competition between two micro-organisms for adhesion sites has been reported (Kennedy and Volz 1985). Taking that into consideration, it would mean that the highly adherent isolates of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this effect was not observed with C. parapsilosis or T. glabrata. Competition between two micro-organisms for adhesion sites has been reported (Kennedy and Volz 1985). Taking that into consideration, it would mean that the highly adherent isolates of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…Competition for the adhesion sites is another form of interaction that may take place between bacteria and yeast cells. Indigenous intestinal microflora reduced the mucosal adhesion of C. albicans to the gastrointestinal tract of Syrian hamsters by forming a dense layer of bacteria in the mucus gel, outcompeting yeast cells for adhesion sites, and producing substances inhibitory to the adhesion of C. albicans (Kennedy and Volz 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Similar effects of antibacterials have been reported in a number of previous studies, where increased attachment of yeasts to epithelial cells was noted after the administration of antibiotics. 18,19 One reason for this is thought to be the elimination of bacterial species which competitively inhibit candidal adhesion to the buccal mucosa. Liljemark and Gibbons, 20 using gnotobiotic rats, demonstrated that the presence of oral bacterial species on epithelial surfaces reduces the subsequent adherence of C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…29 It has been suggested that most systemic candidal infections are endogenously acquired from the gastrointestinal tract. 30 Most studies addressing the use of probiotics for the treatment of intestinal disorders are related to inflammatory bowel diseases such as Crohn disease and ulcerative colitis or antibiotic-associated diarrhoea where probiotics are already used as therapeutics.…”
Section: Intestinal Candida Colonisationmentioning
confidence: 99%